SIKLUS HIDUP PERUSAHAAN DAN PENGHINDARAN PAJAK - Eddy Suranta; Pratana Puspa Midiastuty; Vika Fitranita; Andini Tiara Dianty (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2021)
The purpose of this study is to provide empirical evidence of the influence of the company's life cycle which is classified based on cash flow patterns on tax avoidance as measured by the effective tax rate (ETR). This study uses financial statement data from non-financial companies listed on the Indonesia Stock Exchange (IDX) with an observation period of 2012-2018. The method used in sample selection is the purposive sampling method and the number of observations used in the study of 1180 observations. The hypothesis proposed in this study will be tested using logistic regression. The logistic regression results prove that companies at the introduction stage tend to avoid lower taxes. The results of subsequent studies prove that companies at the growth and mature stages avoid greater tax avoidance than at the introduction stage and decline, companies tend not to avoid taxes.